2020
DOI: 10.1021/acs.jpcc.0c01916
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Cation Electrolytes for High-Power and High-Energy LTO//AC Hybrid Capacitors

Abstract: Dual-cation electrolyte systems, which contain two cations [Li + and spiro-1,1′-bipyrrolidinium (SBP + ), are proposed to enhance the power capability of hybrid capacitors composed of thick Li 4 Ti 5 O 12 (LTO) negative (200 μm) and activated carbon (AC) positive electrodes (400 μm), which thus reduces the resistive overvoltage in the system. Detailed studies of the mass transport properties based on the combination of spectroscopy and electrochemical analysis have shown that the presence of SBP + , despite sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…The SBP-based dual-cation system (1 M LiBF 4 + 2 M SBPBF 4 /PC) enhanced the power density owing to its higher ionic conductivity (7.7 mS cm –1 ) than the single-cation electrolytes (1 M LiBF 4 /PC, 3.4 mS cm –1 ). We also revealed that such increase in the “total” ionic conductivity associated with all electrolyte ions (Li + , SBP + , and BF 4 – ) brought about the acceleration of the charge-transfer reaction at the LTO/electrolyte interface (lithiation/delithiation of LTO), despite the decreased “individual” ionic conductivity of Li + …”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…The SBP-based dual-cation system (1 M LiBF 4 + 2 M SBPBF 4 /PC) enhanced the power density owing to its higher ionic conductivity (7.7 mS cm –1 ) than the single-cation electrolytes (1 M LiBF 4 /PC, 3.4 mS cm –1 ). We also revealed that such increase in the “total” ionic conductivity associated with all electrolyte ions (Li + , SBP + , and BF 4 – ) brought about the acceleration of the charge-transfer reaction at the LTO/electrolyte interface (lithiation/delithiation of LTO), despite the decreased “individual” ionic conductivity of Li + …”
Section: Introductionmentioning
confidence: 82%
“…Furthermore, we performed EIS measurements on the SOC-controlled LTO//LTO symmetric laminate-type cells (Figure S1c, a 4-electrodes cell, SOC = 25%) to evaluate the R ct of the LTO electrodes. Detailed information on the preparation process of the 4-electrodes cell, which has the advantage of not unnecessarily disassembling the cells before the EIS measurements (Figure S1c), is described in our previous paper . The EIS measurements were conducted at T = 298 K with a perturbation signal of ± 10 mV in the frequency range of 0.01–65.5 kHz.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the energy density is insufficient. A metal-ion battery, on the other hand, has high energy density, but the power density is low. Under these circumstances, “supercapattery” is becoming popular as a new type of energy storage device. Supercapattery is defined as a combination of a supercapacitor and a battery and expected to achieve high energy density, high power density, high-rate charge storage capability, and longer charge/discharge durability. It is different from a metal-ion capacitor, composed of a battery-type anode and a capacitor-type cathode, or a hybrid capacitor, made of the combination of an electrical double-layer capacitor (EDLC) and a pseudocapacitor. In addition, to date, research has been focused on developing flexible energy storage for wearable electronics that can deliver good performance under folded or bent conditions. , However, the low ion mobility, poor reversibility, and inactivation in flexible energy storage are major concerns for the durability.…”
Section: Introductionmentioning
confidence: 99%